Mild Mechanic Stimulate on Acupoints Regulation of CGRP-Positive Cells and Microglia Morphology in Spinal Cord of Sciatic Nerve Injured Rats - Yi-zhen, Li; Run-pei, Miao; Tian-yuan, Yu; Wan-zhu, Bai; Jing-jing, Cui; Meng-qian, Lu; Yi, Shen; Yu-ting, Luo; Shuai, Shao; Yu-mo, Zhang; Yan-jun, Mo; Tao-tao, Lv; et al. (Frontiers in Integrative Neuroscience, 2019)
Objective The objective of this study is to observe the effects of mild mechanical stimulation on acupuncture points of spinal motor neurons and active substances of sciatic nerve injury in rats, and to explore the morphological basis for the recovery of motor function in rats with sciatic nerve injury, using mild acupuncture. Acupuncture in the local area of injury may cause further damage to the peripheral nerve injury. We believe that mild mechanical stimulation on the surface, using some specific acupuncture points can also have a positive effect on nerve repair. This method, called Chinese tuina, has existed for more than 2,000 years in China. Methods This study establishes a rat model using sciatic nerve crush injury. Rats received Chinese tuina in accordance with the principle of the three methods and three points, once a day, for 20 days. The rats’ status of hindlimb recovery was detected by a sciatic functional index. The labeled neuronal cell body was used to evaluate the fiber recovery after the rats’ sciatic nerve injury, using a neural tracing technique. Our team studied motor neuronal cell bodies, CGRP-positive cells, and the microglia of damaged sciatic nerves which were stained with fluorescent triple staining, adopting a confocal multi-layer scanning technique, and then the changes in neuronal activity distribution and expression, and changes of time and treatment were described, using the method of morphological description. Results Sciatic nerve injury decreased the survival rate of motor neurons, affected CGRP-positive cells, and activated microglia in the ventral horn of the spinal cord. Compared with the model group, the survival of spinal ventral horn motor neurons was increased through tuina intervention. The swelling of CGRP-positive cells was alleviated, and the degree of microglia activation was less than that of the model group. Conclusion This study used visual morphological findings to assess changes in neurons and active substances with time after injury of the peripheral nerve, and demonstrated that peripheral mild acupuncture intervention improved the capacity of neurofibrillary axoplasmic transport, regulated microglia activation, and significantly promoted the recovery of sciatic nerve injury.